The Sociolingustics Analysis of Address Terms in English and Enrekang Durinese - Nurfitriana Zainal; Noer Jihad Saleh; Harlinah Sahib (Hasanuddin University, 2022)
This research is a sociolinguistics study which explore the relationship between language and society. The aims of the research is to identify the kind of address terms used in English and Enrekang Durinese based on daily conversation. The research method used in this research is descriptive qualitative. The Enrekang Durinese data is obtained by Recording and interviewing which is done by Massenrempulu people in Duri, Alla’ Sub-district, Enrekang District. The English data is obtained from English Movie and Series which contain utterance of address terms.The result of the research shows the kind of address terms used in English and Enrekang Durinese in daily conversations. They are: 1) Pronoun (Second Person Pronoun) 2) Kinship Terms and 3) Non-Kinship Terms. The difference from the both languages appeared in Pronoun, Enrekang Durinese has two type of Pronoun, Polite and Polite while In English, there is only one second person pronoun; you. Another difference found in kinship and non-kinship terms. Enrekang Durinese people usually use mockery to address family and relative while using mockery to address family and relative is not found in English Data. Another result found in this research is there are aspects that influence the use of the address terms in English and Enrekang Durinese, they are 1) Sex and Age 2) Situation 3) Social Rank/ Social status.